The Development of A Transformative Learning Model and Its Influence on The Social Behavior Of Street Children at “Rumah Singgah” Surabaya - NurSekti, Marita; Sujarwo (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2025)
This study aims to develop a transformative learning model to facilitate social behavior change among street children at Rumah Singgah Kampung Anak Negeri Surabaya. The research adopts the Research and Development (R&D) approach, using the ADDIE model, which comprises Analysis, Design, Development, Implementation, and Evaluation. The study subjects are foster children at UPTD Kampung Anak Negeri Surabaya. Data were collected through interviews, questionnaires, and observations, then analyzed descriptively using the Goodman statistical method. The findings indicate that the transformative learning model is effective in improving the social behavior of street children through four key stages: real-life experience, reflection, conceptualization, and implementation. The implementation of this model has yielded positive outcomes, marked by a decrease in rebellious behavior, increased participation in learning activities, and improved socialization skills. The study’s implications suggest that the transformative learning model can serve as an effective approach for education and rehabilitation programs for street children in Indonesia. Keywords: learning models, transformative, street children, social behavior, halfway house